Assessment of Disaster Preparedness and Response Capability Among Paramedics in Arar City, KSA: A Cross-Sectional Study - Meshal Salem Al Dahmashy,; Musa Hailan Al-Anazi,; Naif Mofareh Alshammari,; Nada Ramadan A Albathali,; Fahad Khameis AlShamerey, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: This study aimed to assess the level of disaster preparedness and response capability among paramedics in Arar City, Kingdom of Saudi Arabia (KSA). Methods: A cross-sectional survey was conducted among a random sample of 120 paramedics from 3 hospitals in Arar City. The Disaster Preparedness Evaluation Tool (DPET), a validated 36-item questionnaire, was used to measure knowledge, skills, and attitudes related to disaster preparedness and response. Descriptive and inferential statistics were computed. Results: The response rate was 91.7% (n=55). The mean overall DPET score was 3.47±0.74 out of 5, indicating moderate to high preparedness. Paramedics scored highest on knowledge of triage and evacuation (4.12±0.85), and lowest on familiarity with the hospital's disaster plan (2.86±1.09). Years of experience, previous disaster response participation, and recent training were significantly associated with higher preparedness scores (p<0.05). Key perceived barriers included lack of simulations, inadequate equipment, and poor multi-agency coordination. Conclusions: Paramedics in Arar City reported moderate to high levels of disaster preparedness. However, specific areas for improvement were identified. Findings highlight the importance of regular training, drills, and interprofessional collaboration to enhance paramedics' readiness for effective disaster response. Insights from this study can inform the development of targeted interventions and policies to strengthen the resilience of local EMS systems.